Nanoscale Optical Trapping by Means of Dielectric Bowtie - Giuseppe Brunetti; Nicola Sasanelli; Mario Nicola Armenise; Caterina Ciminelli (Photonics, 2022)
Plasmonic and dielectric tweezers represent a common paradigm for an innovative and efficient optical trapping at the micro/nanoscale. Plasmonic configurations provide subwavelength mode confinement, resulting in very high optical forces, at the expense of a higher thermal effect, that could undermine the biological sample under test. On the contrary, dielectric configurations show limited optical forces values but overcome the thermal challenge. Achieving efficient optical trapping without affecting the sample temperature is still demanding. Here, we propose the design of a silicon (Si)-based dielectric nanobowtie dimer, made by two tip-to-tip triangle semiconductor elements. The combination of the conservation of the normal component of the electric displacement and the tangential component of the electric field, with a consequent large energy field confinement in the trapping site, ensures optical forces of about 27 fN with a power of 6 mW/µm2. The trapping of a virus with a diameter of 100 nm is demonstrated with numerical simulations, calculating a stability S = 1, and a stiffness k = 0.33 fN/nm, within a footprint of 0.96 µm2, preserving the temperature of the sample (temperature variation of 0.3 K).